Subjective Cognitive Complaints in Distant Phase After Stroke – Preliminary Study - Małgorzata Szepietowska, E (KnE Life Sciences, 2018)
Introduction. Subjective cognitive decline (SCD) is often reported by healthy individuals and by different clinical groups. Current data do not clearly show the relationship between SCD and cognitive functioning, but the predictors of SCD are: age, depression and sociodemographic factors. Inconclusive data also applies to people suffering from stroke in the distal post-stroke phase. Correct identification of the causes of SCD will help to take adequate forms of psychological therapy (neuropsychological rehabilitation and/or psychotherapy). Methodology. The aims of research was to compare the intensity and structure of SCD as well as their determinants in healthy persons and those after stroke. In our study 193 adults participated: 118 osób without brain pathology and 75 patients who suffered stroke 2–3 years earlier. DEX-S and ProCog as methods of evaluation of SCD and cognitive assessment techniques: the Montreal Cognitive Assessment Scale (MoCA), WAIS-R subtests and intensity of depressive mood (Geriatric Depression Scale – 15) were used in the study. Results. Patients after stroke were characterized by more severe SCD than healthy people. People in both groups likewise (low) rated one’s own long-term memory, general cognitive and executive function. It has also been shown that people after stroke have significantly lower cognitive competencies compared to healthy individuals, but similar (low) level of depressive mood. The later part of the analysis showed that some complaints may be determined by depressive mood, others are due to the interaction of cognitive deficits and depressive mood. Conclusion. Our results confirm the need for proper qualifications complaints in patients after stroke (in distant post-stroke phase). Keywords: subjective cognitive decline, stroke, cognitive functioning, depression